Smart and Seamless Social Commerce: How Platform Design, Perceived Ease of Use, and AI Recommendations Lock in Tokopedia & TikTok Shop Users - Windarko Windarko; Agung Zulfikri (JURNAL ECONOMINA, 2026)
This study investigates the impact of platform design, perceived usability, and AI suggestions on e-retention via e-trust among users of Tokopedia and TikTok Shop. The research employs a quantitative methodology utilising Partial Least Squares Structural Equation Modelling (PLS-SEM). Data were gathered from 200 active users of Tokopedia and TikTok Shop in the Greater Jakarta region using purposive sampling. The results indicate that platform design and perceived usability significantly enhance both e-trust and e-retention. E-trust substantially affects e-retention and somewhat mediates the connections between platform design, perceived ease of use, and e-retention. Conversely, AI recommendations have a substantial impact on e-retention, however they do not markedly alter e-trust. Moreover, e-trust does not facilitate the connection between AI recommendations and e-retention. The findings suggest that appealing platform design and user-centric experiences are the principal factors influencing consumer trust and retention, whereas AI-driven suggestions primarily promote ongoing platform engagement through tailored content. This study enhances the digital commerce literature by emphasising the strategic importance of e-trust in bolstering long-term consumer retention on e-commerce platforms